Comparative Assessment of Water Quality of Tube wells and Pipe Borne Water in Kaluvankeni Hostels, Eastern University, Sri Lanka - Arasaretnam, S.; Cavisana, K. (University of Jaffna, 2020)
This study was carried out to assess the water quality of tube wells and pipe borne water supplied in the hostels of Kaluvankeni, Eastern University, Sri Lanka using physicochemical parameters such as temperature, pH, Electrical Conductivity, Salinity, TDS (Total Dissolved Solids), Total Hardness, Dissolved Oxygen (DO), Turbidity, and quantitative studies of some specific cations (Ca2+, Mg2+, Fe2+, Cr3+, Cd2+, K+) and anions (NO3-, NO2-, PO43-, Cl-, F-). The sampling was carried out for two times per week for four weeks during the period from March to July 2020. Water samples were collected from three stations in hostels and were analyzed separately using standard methods. The results showed that both tube wells exceeded the permissible threshold levels of salinity, DO, turbidity, iron, potassium, and chromium while only tube well 2 exceeded the permissible threshold levels of conductivity. Pipe borne water was within the permissible threshold levels of all the parameters. The root causes for high turbidity in Tube well water was due suspensions from soil due to the frequent drawings from them. High level of iron concentrations could possibly be as a result of corrosions of iron pipes and may be due to the ground water contaminations from burial mounds. The obtained values of each parameter were compared with the standard values set by the World Health Organization (WHO) and Sri Lankan Standard for Drinking water (SLS 614:2013). Overall, the pipe borne water was safe for the consumption while the water from both tube wells were not advisable for consumptions but they can be used for non-consumable purposes.
Keywords: Dissolved Oxygen; Ground water; Physicochemical; Total Hardness